E.Wayne Nafziger - ECONOMIC DEVELOPMENT, 5TH Edition, Cambridge University Press, UK, 2012 - Epure, Manuela (Journal of Economic Development, Environment and People, 2012)
Interested readers can take a look inside of the book at: <a href="http://books.google.ro/books?id=bGxVzEdae7UC&printsec=frontcover&dq=Economic+Development,+Nafzi%20ger&source=bl&ots=qKaeX4KrqA&sig=2wpgv971Igh0DUJrcz4EH–%20TzXE&hl=ro&sa=X&ei=TGVlUJdGzdmyBv2_gdAI&ved" target="_blank">http://books.google.ro/books?id=bGxVzEdae7UC&printsec=frontcover&dq=Economic+Development,+Nafzi <a href="http://books.google.ro/books?id=bGxVzEdae7UC&printsec=frontcover&dq=Economic+Development,+Nafzi%20ger&source=bl&ots=qKaeX4KrqA&sig=2wpgv971Igh0DUJrcz4EH–%20TzXE&hl=ro&sa=X&ei=TGVlUJdGzdmyBv2_gdAI&ved" target="_blank">ger&source=bl&ots=qKaeX4KrqA&sig=2wpgv971Igh0DUJrcz4EH– <a href="http://books.google.ro/books?id=bGxVzEdae7UC&printsec=frontcover&dq=Economic+Development,+Nafzi%20ger&source=bl&ots=qKaeX4KrqA&sig=2wpgv971Igh0DUJrcz4EH–%20TzXE&hl=ro&sa=X&ei=TGVlUJdGzdmyBv2_gdAI&ved" target="_blank">TzXE&hl=ro&sa=X&ei=TGVlUJdGzdmyBv2_gdAI&ved